Animal Model Used in Dentistry-A Review - R.Kushali 1, Subhabrata Maiti2 , R.V.Geetha3 , Jessy4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The main aim of the study was to know about the various dental studies carried out on animal models. Animalshave been targeted for various medical investigations for human observations. From the early nineteenth century,there was a significant increase in the use of animals for scientific experiments . Compared to small animal modelslike rodents, large animal models are superior in many aspects for the study of human diseases and pre-clinicaltherapies.This is significant to develop new medicines for newer diseases emerging day by day in the current world.Animals are also used for the safety test to know the potential of medicines before they are being clinically introducedin suffering patients to make sure it doesn’t show adverse effects and to check the safety of other chemicals as well.A review is done on different dental studies carried out in animal models which were collected from search engineslike pubmed , google scholar, google chrome and from various research articles.Quality analysis was done usingthe ideal method. The review helps in attaining complete knowledge about dental related studies on animal models.Studies like these can prove to be helpful in further development concerned with humans. This review gives a clearview about the different dental studies carried out in animal models and it’s observation and outcomes.